Natural Variation in Ovule Morphology Is Influenced by Multiple Tissues and Impacts Downstream Grain Development in Barley (Hordeum vulgare L.) - Wilkinson, Laura G.; Yang, Xiujuan; Burton, Rachel A.; Würschum, Tobias; Tucker, Matthew R. (Frontiers in Plant Science, 2019)
The ovule plays a critical role in cereal yield as it is the site of fertilization and the progenitor of the grain. The ovule primordium is generally comprised of three domains, the funiculus, chalaza and nucellus, which give rise to distinct tissues including the integuments, nucellar projection and embryo sac. The size and arrangement of these domains varies significantly between model eudicots, such as Arabidopsis thaliana, and agriculturally important monocotyledonous cereal crops, such as Hordeum vulgare (barley). However, the amount of variation in ovule development among genotypes of a single species, and its functional significance, remains unclear. To address this, wholemount clearing was used to examine the details of ovule development in barley. Nine sporophytic and gametophytic features were examined at ovule maturity in a panel of 150 European two-row spring barley genotypes, and compared with grain traits from the preceding and same generation. Correlations were identified between ovule traits and features of grain they produced, which in general highlighted a negative correlation between nucellus area, ovule area and grain weight. We speculate that the amount of ovule tissue, particularly the size of the nucellus, may affect the timing of maternal resource allocation to the fertilized embryo sac, thereby influencing subsequent grain development.